Entrepreneurial experience, support for community and family firm performance - Fahed-Sreih, Josiane (2016)
Drawing on theories from corporate social responsibility, entrepreneurship, and human capital, this study examines the structural relationships between entrepreneurial experience, support for community and family firm performance. Partial least-squares structural equation modeling (PLS-SEM) was used to collect the data from 176 family businesses from two sectors of the economy - product-manufacturing and service-based organizations. The empirical results indicated that family firm owners’ entrepreneurial experience (business owner’s education level, length of time as a business owner, and the number of businesses owned in the past) is a significant predictor of the business’ support for community. Entrepreneurial experience was also found to have a significant and indirect effect on family firm performance. Additionally, the structural model was examined across product and service-based organizations. Our findings suggest that entrepreneurial experience has a stronger effect on family firm performance among service-based organizations.